Enhanced efficiency of swine wastewater treatment by the composite of modified zeolite and a bioflocculant enriched from biological sludge. Issue 23 (2nd December 2018) - Guo, Junyuan; Du, Jiali; Chen, Peilan; Huang, Xinyi; Chen, Qingyang
ABSTRACT: A high-ammonia-resistant strain was firstly isolated from activated sludge and applied to harvest a bioflocculant from a swine wastewater. Enhancement of swine wastewater treatment was investigated by a composite of the harvested bioflocculant and a zeolite modified by integrating calcinations with MgO at 400°C. Results have demonstrated that 71.8% of Chemical Oxygen Demand (COD), 54.5% of ammonia, and 81.2% of turbidity can be removed from the swine wastewater by the bioflocculant alone. Results have also demonstrated that 73.4% of ammonia could be removed from the swine wastewater by the modified zeolite alone, while almost no COD was removed. Thus, the bioflocculant and modified zeolite were used simultaneously to enhance swine wastewater treatment, and response surface methodology (RSM) was employed to optimize the treatment process. Under the optimal treatment conditions of bioflocculant of 12 mg/L, modified zeolite of 8 g/L, pH of 7.5, and agitation speed of 200 r/min, obtained by the RSM, 88.6% of COD, 85.8% of ammonia, and 95.5% of turbidity could be removed from swine wastewater, which were significantly improved compared with that by the bioflocculant or modified zeolite alone. The use of the composite exerted advantages of the bioflocculant and modified zeolite, and provided a feasible way to improve pollutants' removal from wastewaters.